KESALAHAN PENGGUNAAN AFIKSASI DI MEDIA SOSIAL INSTAGRAM: KAJIAN MORFOLOGIS - Nia Agustina; Mahsun Mahsun; Muhammad Sukri (El-Tsaqafah : Jurnal Jurusan PBA, 2023)
This study investigates the inaccuracy of utilizing affixes on Instagram social media based on morphological investigations. This is a qualitative study based on normative norms derived from conventional Indonesian grammar. The data in this study are attached words that exhibit abnormalities in their use on the Instagram social media platform. This study’s data collection method includes observation, documentation, and notes. Furthermore, the data analysis method employs the intralingual equivalent method. Based on data analysis, this study’s findings reveal errors in afiixation process, including prefixation, suffixation, and confixation errors. On prefixation errors, there are prefix errors {m??-}, prefix errors {p??-}, prefix errors {p?r-}, prefix errors {b?r-}, and prefix errors {t?r-}. Then the problems in suffixatiion include faults in the suffixes errors {-in}, suffixes errors {-an}, suffixes errors {-kan}, and suffixes errors {-i}. Meanwhile, confixation errors were founded confix errors {k?-an} and confix errors {p??-an}.